2007
DOI: 10.1016/j.cellbi.2007.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant metabolism in Xenopus laevis embryos is affected by stratospheric balloon flight

Abstract: To test the effects of low levels of radiation from space on living organisms, we flew Xenopus laevis embryos at different stages of development on a stratospheric balloon (BI.R.BA mission). After recovery, different parameters were analyzed to assess the effects of flight, with particular regard to oxidative stress damage. Because of failed temperature control during flight, the flight shielded embryos (FC) could not be used for biochemical or morphological comparisons. In contrast, the incubation conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Shielding of the box containing the cells diminished the effect of the stratosphere and reduced the variations in lipid metabolism. The effect of the shielding was also demonstrated in a study performed on X. laevis that participated to the same space mission [12]. The authors demonstrated that the effect of stratosphere depended on the stage of X. laevis development.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Shielding of the box containing the cells diminished the effect of the stratosphere and reduced the variations in lipid metabolism. The effect of the shielding was also demonstrated in a study performed on X. laevis that participated to the same space mission [12]. The authors demonstrated that the effect of stratosphere depended on the stage of X. laevis development.…”
Section: Discussionmentioning
confidence: 90%
“…The authors demonstrated that the effect of stratosphere depended on the stage of X. laevis development. In fact younger embryos were the most affected, with increases in mortality and malformations [12]. Moreover, no induction of HSPs was observed, suggesting that results obtained were caused by the radiation itself and not by general stress occasioned by the balloon flight [12].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations